Study of Correlation of TFT Levels with Severity of Liver Disease in Patients with Cirrhosis of Liver Measured by Child Pugh Score - Vijaykumar , Samarthana; Patil, Mamatha B. (Advancement and New Understanding in Medical Science Vol. 9, 2024)
The intricate interplay between thyroid function, cirrhosis, and liver dysfunction presents a compelling opportunity for scientific and medical advancements. This exploration has multifaceted significance, with a primary focus on revolutionizing clinical diagnosis. The research introduces a promising avenue for novel diagnostic tools, utilizing thyroid function tests to detect cirrhosis early—a groundbreaking prospect that minimizes the risk of severe complications such as liver cancer and improves treatment outcomes. Early diagnosis not only holds clinical benefits but also addresses the economic burden associated with expensive liver transplants, often inaccessible in countries with limited healthcare coverage. This research becomes a pivotal force in reshaping clinical practice, fostering groundbreaking research, and ultimately enhancing the health and well-being of individuals grappling with these interconnected conditions. All patients aged 30-80 years with cirrhosis of liver who are attending Rajarajeshwari Medical College and Hospital. Detailed history, physical examination and drug history was taken as per pre- designed performa. Relevant investigations were done for assessing thyroid function and liver cirrhosis. Severity of liver dysfunction was graded by using Child Pugh Scoring. The prevalence of hypothyroidism among patients with liver cirrhosis was 64%. Majority of the cases had a high TSH and TSH levels were directly correlated severity of liver disease. Total T3 levels were low in majority of the cases and it was inversely correlated with severity of liver disease. FT3 was low in most of the cases with child B and child C score; it was inversely correlated with severity of liver disease. FT3 was found to be a more sensitive marker than total T3 for assessing severity of liver disease. Thyroid dysfunction is widespread in cirrhosis of the liver, hence thyroid function testing should be performed on all cirrhotic patients to assess the severity and prognosis.